2022
DOI: 10.1002/anie.202201791
|View full text |Cite
|
Sign up to set email alerts
|

Mediating Oxidation of Thioethers with Iodine—A Mild and Versatile Pathway to Trigger the Formation of Peptide Hydrogels

Abstract: The development of redox‐triggerable peptide hydrogels poses fundamental challenges, since the highly specific peptide architectures required inevitably limit the versatility of such materials. A powerful, yet rarely applied approach to bypass those barriers is the application of a mediating redox reaction to gradually decrease the pH during hydrogel formation. We report a versatile strategy to trigger the formation of peptide hydrogels from readily accessible acid‐triggerable gelators by generating protons by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 65 publications
(48 reference statements)
0
10
0
Order By: Relevance
“…They can be incorporated as side chains, terminal groups, or linkages connected with conjugates using the amino acid L-methionine or through the etherification of L-cysteine. 23,[55][56][57] The oxidation of ROSsensitive polypeptides also modulates the hydrophobicity and assembly properties leading to different aggregate states, secondary structures and micro/macro-structural properties of the final material. Deming and co-workers studied the selfassembly of amphiphilic peptides consisting of poly(L-methionine) 65 -b-poly(L-leucine 0.5 -stat-L-phenylalanine 0.5 ) 20 , named M 65 (L 0.5 /F 0.5 ) 20 , which showed a-helix conformation in this hydrophobic state.…”
Section: Synthesis and Self-assembly Of Thioether-containing Polypept...mentioning
confidence: 99%
“…They can be incorporated as side chains, terminal groups, or linkages connected with conjugates using the amino acid L-methionine or through the etherification of L-cysteine. 23,[55][56][57] The oxidation of ROSsensitive polypeptides also modulates the hydrophobicity and assembly properties leading to different aggregate states, secondary structures and micro/macro-structural properties of the final material. Deming and co-workers studied the selfassembly of amphiphilic peptides consisting of poly(L-methionine) 65 -b-poly(L-leucine 0.5 -stat-L-phenylalanine 0.5 ) 20 , named M 65 (L 0.5 /F 0.5 ) 20 , which showed a-helix conformation in this hydrophobic state.…”
Section: Synthesis and Self-assembly Of Thioether-containing Polypept...mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10] The reversible sol-gel transition of hydrogels usually triggered by various external stimuli. [11][12][13][14] These stimuli are the key ingredients for controlling the self-assembly behavior of the hydrogelator. [15][16][17] The stimuli responsive property of hydrogel structure [18][19][20][21] is frequently installed into artificial hydrogel system to carry out sol-gel transition for various potential applications including targeted drug release, self-healing, shape memory, and supramolecular adhesion purposes.…”
Section: Introductionmentioning
confidence: 99%
“…Hydrogels are one of the most important multifunctional supramolecular smart emerging materials in the field of current research [1–10] . The reversible sol‐gel transition of hydrogels usually triggered by various external stimuli [11–14] . These stimuli are the key ingredients for controlling the self‐assembly behavior of the hydrogelator [15–17] .…”
Section: Introductionmentioning
confidence: 99%
“…For most LMWGs, the method of gel preparation influences their supramolecular organization, tremendously impacting the properties of the final material. Environmental conditions such as pH, temperature, or ionic strength of the medium can drive changes in the self-assembly pathway of the LMWG through modulating the balance between kinetics and thermodynamics. A more recent strategy to control the self-assembly pathway involves reaction-coupled assembly, namely, the use of chemical bond formation, change, or disruption in situ to trigger the gelation process. More specifically, nongelling precursors outfitted with complementary reactive groups are ligated in the presence of chemical or enzymatic catalysts that provide an additional handle to control the final gel structure and function. Xu and co-workers demonstrated control over the gelation behavior of short peptides through enzymatic catalysis of tyrosine phosphorylation or dephosphorylation reactions by kinases or phosphatases. , Alternatively, Eelkema and van Esch showed that tuning the reaction rate of hydrazone bond formation on nongelling precursors using acid or aniline catalysis results in structural changes in the nanofiber networks with consequent effects on gel stiffness. , …”
Section: Introductionmentioning
confidence: 99%